Remarks on subversive performance at the trial of Giulio Cesare Vanini (1618-19) - Horsley, Adam (Modern Humanities Research Association, 2015)
This article uses the theoretical framework of James C. Scott's Domination and the Art of Resistance (1990) to analyse the trial and execution of Giulio Cesare Vanini (1585–1619). It argues that Vanini's final actions were subversive acts of rebellion and libertinage against Catholic authority during the typically politicized capital punishment of an atheist. By examining accounts of his public and private speech and the reliability of contemporary sources, it demonstrates how Vanini allowed his mask of conformity to drop at his execution in order to enjoy a final moment of freethinking which justifies his contemporary and modern-day reputation as a libertin author and thinker.